2018
DOI: 10.1002/cnma.201800286
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gelation of Graphene Oxide Aqueous Dispersion Induced by Sonication‐Promoted Leuckart Reaction

Abstract: Graphene oxide (GO) undergoes a rapid gelation process in the presence of ammonium hydroxide and formic acid at room temperature which is promoted by ultrasonication. Infrared and X‐ray photoelectron spectroscopy proved partial reduction of GO and nitrogen incorporation, resulting from sonication‐promoted Leuckart reactions at GO carbonyl groups. The amine groups produced via Leuckart reactions undergo further reactions that result in salt bridges with carboxylic groups and covalent cross‐links, both of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The in-and out-of-plane bending vibrations of rings contribute to bands observed in the 505-1088 cm −1 and 417-830 cm −1 , respectively [42] (Figure 2a). The characteristic bands of GO are clearly visible at 1068, 1612 and 1724 cm −1 for bis (PABA) ZrPc/GO and at 983, 1071, 1612 and 1725 cm −1 for bis (DABA) ZrPc/GO [43].…”
Section: Of 13mentioning
confidence: 96%
“…The in-and out-of-plane bending vibrations of rings contribute to bands observed in the 505-1088 cm −1 and 417-830 cm −1 , respectively [42] (Figure 2a). The characteristic bands of GO are clearly visible at 1068, 1612 and 1724 cm −1 for bis (PABA) ZrPc/GO and at 983, 1071, 1612 and 1725 cm −1 for bis (DABA) ZrPc/GO [43].…”
Section: Of 13mentioning
confidence: 96%
“…97 This type of reaction has also been employed to form GO gel in the presence of ammonium hydroxide (NH 4 OH) and formic acid (HCOOH), by which the produced amines are attributed to the gelation. 98 Fig. 5 illustrates the general scheme of converting ketone to amine moieties, and the typical mechanism of one-pot reduction and surface modification of GO counterparts.…”
Section: Covalent Modification Of Go and Rgomentioning
confidence: 99%
“…However, these reagents suffer from rather limited reduction efficiency resulting in the reported C/O atomic ratios of the obtained NRGOs below 8. Recently, we have found that GO can be readily partially reduced (G/O∼2 to 3) with covalent incorporation of nitrogen in the graphene lattice using ammonium formate as reagent at ambient conditions forming a weakly bonded hydrogel . Our finding indicates that ammonium formate would be a better candidate than ammonia/ammonium hydroxide which was inactive under the same ambient conditions.…”
Section: Introductionmentioning
confidence: 82%